Analysis Of Total Dissolved Solids, Color And Specific Volume Of Biscuits With Banana Flour (Musa Acuminata Colla) Substitution And Purple Sweet Potato Puree (Ipomoea Batatas L.) Addition - Jubelito Simanungkalit, Ferlando; Hotman Manurung (Jurnal Scientia, 2024)
This study aims to study the effect of substitution of lady finger banana flour (Musa acuminata colla) and the addition of purple sweet potato (Ipomoea batatas L.) on the total soluble solids, color and specific volume of biscuits. This study was conducted experimentally using a completely randomized factorial design. The first factor was the ratio of wheat flour to lady finger banana flour (100:0%; 75:25%; 50:50% and 25:75%). The second factor was the addition of purple sweet potato puree (0%, 25%, 50% and 75%). The parameters analyzed consisted of: total soluble solids, color: brightness (L), reddish (a) and yellowish (b) and specific volume. The results showed that the ratio of wheat flour to lady finger banana flour had a very significant effect on the total soluble solids of biscuits 12.750 - 16.083 oBrix, brightness (L) 31.730 - 49.146; redness (a) 11.911 – 22.836; yellowness (b) 2.586 – 26.891. The addition of purple sweet potato puree gave a very significant effect on the total soluble solids of biscuits 13.417 – 15.125 oBrix, brightness (L) 35.447 – 46.319; redness (a) 17.794 – 20.257; yellowness (b) 7.377 – 15.559. The interaction between the ratio of wheat flour to banana flour and the addition of purple sweet potato puree gave a very significant effect on the parameters of brightness (L), redness (a) and yellowness (b).